Trade, foreıgn dırect ınvestments, research and development, human capıtal and technology dıffusıon ın turkısh manufacturıng sector - Özşahin, Gülşah (My University, 2017)
Bu tezde, Türkiye imalat alt-sektör düzeyinde uluslararası ticaretin (ihracat ve ithalat), doğrudan yabancı yatırımların, teknolojik gelişmelerin (teknoloji difüzyonu ve Ar-Ge çalışmaları) ve beşeri sermayenin verimlilik değişimine etkisi incelenmiştir. ABSTRACTIn this thesis, the effects of international trade (exports and imports), foreign direct investments, technological developments (technology diffusion and R&D studies) and human capital on change in productivity are examined in the manufacturing sub-sectors in Turkey.
Keywords: araştırma ve geliştirme; beşeri sermaye Change in productivity; Dış ticaret; foreign direct investments; human capital; international trade; research and development; technology diffusion; teknoloji difüzyonu; Ticaret; Türkiye; Verimlilik değişimi; yabancı doğrudan yatırımlar; Yatırımlar, Yabancı